Hadith #2957 - Sunan Abi Dawud - Ahmed bin Abi al-Hawari أحمد بن عبد الله بن ميمون; Slym bin Mtyr سليم بن مطير (Sunan Abi Dawud)
That Ibn ‘Umar was presented before the Prophet (ﷺ) on the day of Uhud, when he was fourteen years old, but he did not allow him. He was again presented to him on the day of Khandaq (the battle of Trench) when he was fifteen years old, he allowed him.
Grade: Sahih

Hadith #2958 - Sunan Abi Dawud - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Slym bin Mtyr سليم بن مطير (Sunan Abi Dawud)
Sulaym ibn Mutayr reported on the authority of his father that Mutayr went away to perform hajj. When he reached as-Suwaida’, a man suddenly came searching for medicine and ammonium anthorhizum extract, and he said: A man who heard the Messenger of Allah (ﷺ) addressing the people commanding and prohibiting them, told me that he said: O people, accept presents so long as they remain presents; but when the Quraysh quarrel about the rule, and the presents are given for the religion of one of yo
Grade: Da'if